Note sur la gestion des portefeuilles de placements - Fortin, Franceline (Assurances, 1985)
An insurance portfolio must be compatible with the company, and certain general rules must be followed. This is the approach taken by Mrs. Fortin in this article which is, in fact, an introduction to investment portfolio management.